AB0297 Predictors of an inadequate response to treatment in latin american patients with early rheumatoid arthritis. (12th June 2018) - Gamboa-Cárdenas, R.V.; Ugarte-Gil, M.; Massardo, L.; Sacnun, M.P.; Granel, A.; Catoggio, L.; Lima-Corrêa, F.A.; Appenzeller, S.; Azevedo, A.; Keiserman, M.; Rueda, J.; Zurita, L.; et al.
Abstract : Background: Inadequate response to treatment in early rheumatoid arthritis (RA) is associated with adverse consequences. We have previously shown high baseline levels of disease activity in Latin American RA patients. 1 Objectives: To identify the baseline predictive factors of inadequate response to treatment in patients with early RA from a GLADAR cohort, at one year from cohort entry. Methods: GLADAR cohort includes 1093 consecutive RA patients with disease <1 year from 46 centres in 14 Latin American countries. For these analyses, patients with complete clinical and laboratory assessments with DAS28-ESR>3.2 at the baseline, and one-year follow up visits were included. Inadequate treatment response was ascertained with the EULAR definition which is based on DAS28-ESR obtained at one-year of follow up [a variation ≤0.6 in any category of activity (mild, moderate or severe) and a variation >0.6 but≤1.2 in the high activity category]. Gender, age at diagnosis, diagnosis delay, socioeconomic status (by the Graffar scale), ethnicity, medical coverage, rural origin, rheumatoid factor (RF) positivity, disability (HAQ-DI), DMARDs use, corticosteroid use, and DMARD treatment delays were examined as potential predictive factors of this outcome. Univariable and multivariable binary logistic regression models, using a stepdown technique were examined in order to determine the predictors of response at 1 year. Results: Four hundred and forty-eight patients were included. Three hundred and eighty-five (85.9%) were female; the mean (SD) age at diagnosis was 46.1 (13.6) years; 78.3% had medical coverage and 347 patients (77.5%) were RF positive. The mean baseline DAS28-ESR was 6.3 (1.4). EULAR response was met by 347 (77.5%) patients at 1 year. Three hundred patients (67%) have received glucocorticoids, 78.8% at least one DMARD and only 1.1% had received at least one biologic compound. The baseline HAQ-DI was 1.5 (0.0–3.0). Predictors of non-EULAR response at 1 year were: female gender (OR=2.4; CI:1.0–5.6; p=0.039), a higher baseline HAQ-DI (OR=1.7; CI:1.2–2.4; p=0.003) whereas protective factors were higher DAS28-ESR (OR=0.6; CI:0.4–0.7; p<0.001) and having medical coverage (OR=0.5; CI:0.3–0.9; p=0.025). Conclusions: We have identified baseline predictors of adverse response to treatment in LA patients with early RA. Absence of medical coverage seems to be an additional adverse factor associated with poor results. Other factors such as early response/remission or adherence to treatment should be taken into account. Reference: [1] Massardo L. Arthritis Care Res (Hoboken)2012;64(8):1135–4. Disclosure of Interest: None declared